A Randomized Controlled Trial With Mean 16-Year Follow-up Comparing Hamstring and Patellar Tendon Autografts in Anterior Cruciate Ligament Reconstruction. (September 2016) - Björnsson, Haukur; Samuelsson, Kristian; Sundemo, David; Desai, Neel; Sernert, Ninni; Rostgård-Christensen, Lars; Karlsson, Jón; Kartus, Jüri
Background: There is no consensus in the current literature on which surgical options render the best long-term results after anterior cruciate ligament (ACL) reconstruction in terms of clinical outcomes and the development of radiographic osteoarthritis (OA). Purpose: To investigate the long-term clinical and radiographic results after ACL reconstruction using either a patellar tendon (PT) autograft or a hamstring tendon (HT) autograft. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: This multicenter study was based on 2 previous randomized cohorts consisting of 193 patients who underwent unilateral primary ACL reconstruction using either a PT autograft or an HT autograft. The index surgical procedure was performed between September 1995 and January 2000. Clinical assessments, including knee laxity measurements, functional outcomes, patient-reported outcomes, and bilateral standing radiographs, were performed at the final follow-up examination. Results: At the long-term follow-up, 147 (76%) patients were examined: 61 in the PT group and 86 in the HT group. The mean (±SD) follow-up time was 191.9 ±15.1 months for the HT group and 202.6 ± 10.4 months for the PT group. Knee laxity measurements revealed significantly more patients with a normal pivot-shift test finding in the HT group compared with the PT group (71% vs 51%, respectively; P = .048); however, no significant differences were found in terms of the manual Lachman test or the KT-1000 arthrometer manual maximum test. The patients in the PT group had significantly more difficulty knee walking ( P = .049). There were no significant differences between the study groups in terms of patient-reported outcomes or range of motion in the reconstructed knee. In both groups, significantly more signs of radiographic OA were found in the reconstructed knee than in the contralateral healthy knee. However, there were no significant differences between the groups in terms of radiographic OA. Conclusion: Only minor and mostly insignificant differences were found between the PT and HT autograft groups in this long-term randomized controlled trial. In both groups, significantly more signs of radiographic OA were found in the reconstructed knee than in the contralateral knee.